(untitled) (Thành phố Hồ Chí Minh, 2014)
Giới thiệu về tiểu sử, cuộc đời và sự nghiệp của Nữ hoàng Ai Cập Cleopatra
Keywords: Egypt,Ai Cập; History,Tiểu thuyết,Lịch sử,Tiểu thuyết; 332-30 B.C,332-30 TCN